2020
DOI: 10.3390/ijms21061940
|View full text |Cite
|
Sign up to set email alerts
|

How Does Epstein–Barr Virus Contribute to Chronic Periodontitis?

Abstract: Chronic periodontitis is spreading worldwide and mutually interacts with systemic diseases like diabetes mellitus. Although periodontopathic bacteria are inevitable pathogens in their onset and progression, many cases are not ascribable to the virulence of these bacteria because the effect of plaque control is limited. In contrast, Epstein–Barr virus (EBV) in the periodontium has been correlated with chronic periodontitis and has recently been considered as a promising pathogenic candidate for this disease. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
1
21
1
8
Order By: Relevance
“…Regarding the prevalence of CMV, this virus could increase the severity of periodontitis. 23 Although the present study did not obtain significant results for the presence of Porphyromonas intermedia together with CMV as it was found only in 8% of the analyzed literature, periodontopathogens such as Porphyromonas gingivalis (28%) and Tannerella forsythia (16%) stand out. These findings are consistent with those of Imbronito et al, 24 suggesting that CMV and Tannerella forsythia coinfection is more prevalent in patients with chronic periodontitis than in periodontally healthy individuals.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Regarding the prevalence of CMV, this virus could increase the severity of periodontitis. 23 Although the present study did not obtain significant results for the presence of Porphyromonas intermedia together with CMV as it was found only in 8% of the analyzed literature, periodontopathogens such as Porphyromonas gingivalis (28%) and Tannerella forsythia (16%) stand out. These findings are consistent with those of Imbronito et al, 24 suggesting that CMV and Tannerella forsythia coinfection is more prevalent in patients with chronic periodontitis than in periodontally healthy individuals.…”
Section: Discussioncontrasting
confidence: 77%
“…These findings are consistent with those of Imbronito et al, 24 suggesting that CMV and Tannerella forsythia coinfection is more prevalent in patients with chronic periodontitis than in periodontally healthy individuals. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Regarding HSV, Kazi et al,12 detected the presence of HSV-1 and HSV-2 in patients with severe chronic periodontitis, reporting a prevalence of HSV-1 in 52% of the cases, and HSV-2 in 56%. In this review, HSV was the virus least studied in the articles, being found only in 10 publications, although, paradoxically, it has a prevalence of 40%.…”
Section: Discussionmentioning
confidence: 99%
“…EBV produces EBV nuclear antigen (EBNA) and latent membrane protein (LMP) gene products during latency. These include EBNA1, EBNA2, EBNA3A, EBNA3B, EBNA3C, EBNA leader protein, LMP1, and LMP2, which mediate the transforming role of EBV in B cells [ 10 ].…”
Section: Ebv Biologymentioning
confidence: 99%
“…Periodontitis is a poli-microbial disease triggered by dysbiosis of the oral biota. Although the mouth harbors distinct habitats comprising one of the most diverse microbial communities of the human body, Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis are key low-abundance periodontal bacteria that, when over-grown, can bring these ecosystems to a dysbiotic state, particularly the gingiva [ 183 ]. An association between EBV and P. gingivalis in juvenile periodontitis has also been suggested [ 184 ].…”
Section: Ebv Interactions With Oral Bacteria May Facilitate Viral Transmission and Promote Periodontal Diseasesmentioning
confidence: 99%